Implementation of dynamic vehicular rerouting, vehicular safety and pollution reduction techniques using VANET - Arnab, Sandipan Paul; Islam, Md. Shahidul (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.